Implications of E-Commerce and Fintech on Changes in Consumption Patterns in Generation Z Consumers Case Study: Shopee and Brimo Application Users in Bojonegoro Regency (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to find out the influence of the implications of E-Commerce and Fintech on changes in consumption patterns of generation z. In this study, a quantitative approach was used with the data collection used to distribute questionnaires to users of the Shopee and BRImo applications in Bojonegoro Regency with techniques Purposive sampling, a sample that is taken based on certain criteria or characteristics chosen by the researcher. The results of the study show that E-commerce has an effect on changes in the consumption pattern of generation z in Bojonegoro Regency. Meanwhile, Fintech has no effect on changes in the consumption pattern of generation z in Bojonegoro Regency.